PENGARUH KADAR STIMULAN TERHADAP PRODUKTIVITAS GET AH PO HON PINUS (Pin us merkussi Jungh. et de Vriese) PADA BERBAGAI TINGKAT UMUR DI DAERAH SUMEDANG, JAWA BARAT - Erra Yusnita; S Sumadiwangsa; Dendi Setyawan; Erik Dahlian (Pusat Penelitian dan Pengembangan Hasil Hutan, 2001)
Pine (Pinus merkusii Jungh et.de. Vriese) trees have an important role on related industries endeavoring in forest products, due to the widespread utlilization on their potential wood as well as gum matters.Production of pine gum can be affected by the manner of its tapping, kind and percentage of stimulant agent, age and diameter of trees. and genotype factors. Related as such, this investigation was intended lo evaluate the effect of pine tree diameters and stimulant percentage on productivity of pine tapping. In addition, this investigation was also to evaluate whether the tapping orientations (i.e. north. east, south, and westdirections) affected the gum productivity. The main aim was to find out which tapping manner turned out to be the most efficient, the most economic and the safest either lo the trees or to the tapping worker themselves and end up with the optimum and continuity of pine gum production. The pine trees selected for this investigation were the ones growing in Sumedang region, West Java (Indonesia).Results revealed that age of pine trees significantly affecfed the gum production. Tree age of 16, 26 and 31 year old produced gum at 50.15 gr, 81.94 gr, and 9. l7 gr respectively per tree stand. Meanwhile productivity was also affected by tapping orientation, in which the east direcfion of tapping on 16 year old pine tree at stimulant level of either 15% or 20% brought about the optimum productivity. Likewise, optimum production was obtained from 26year old pine tree at 15% stimulant percentage with north as well as southdirection of tapping, and frorn the 31 year old pine free stands at 25% stimulant by westdirection tapping.